2011
DOI: 10.1016/j.ijindorg.2010.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Can real-effort investments inhibit the convergence of experimental markets?

Abstract: Evidence shows that real-effort investments can affect bilateral bargaining outcomes. This paper investigates whether similar investments can inhibit equilibrium convergence of experimental markets. In one treatment, sellers' relative effort affects the allocation of production costs, but a random productivity shock ensures that the allocation is not necessarily equitable. In another treatment, sellers' effort increases the buyers' valuation of a good. We find that effort investments have a short-lived impact … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…Bartling et al (2014) examined markets where the buyer had the market power, and found that sellers were less willing to engage in costly punishment following a low price when the price was chosen in an apparently procedurally fair way (via competitive auction) than otherwise (dictated by the buyer). Still other studies have found that fairness can matter in markets with moral hazard (Fehr et al 1993), adverse selection (Renner and Tyran 2004), and where seller costs are based on performance on a real-effort task (Cason et al 2011).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Bartling et al (2014) examined markets where the buyer had the market power, and found that sellers were less willing to engage in costly punishment following a low price when the price was chosen in an apparently procedurally fair way (via competitive auction) than otherwise (dictated by the buyer). Still other studies have found that fairness can matter in markets with moral hazard (Fehr et al 1993), adverse selection (Renner and Tyran 2004), and where seller costs are based on performance on a real-effort task (Cason et al 2011).…”
Section: Relevant Literaturementioning
confidence: 99%
“…Each buyer's valuation of the good is v (= 21.40 EUR in our experiment), each seller's cost is 0. Buyers and sellers may differ in the extent to which they (1) dislike an unequal distribution of the surplus from trade (see Franciosi et al 1995;Borck et al 2002;Cason et al 2011) and (2) internalize the externalities they generate by trading with each other. Suppose each buyer and seller has a type t distributed with full support on [0, 1] according to a cumulative distribution function G(t).…”
Section: Model and Hypothesesmentioning
confidence: 99%
“…The Encryption task involves matching elements from one set to elements in another set according to a matching rule. This real-effort task is widely adopted in the literature (Cason, Gangadharan, and Nikiforakis, 2011;Charness, Masclet, and Villeval, 2014;Erkal, Gangadharan, and Koh, 2018).…”
Section: Manual Modementioning
confidence: 99%